(untitled) (Journal of Student Affairs in Africa, 2021)
This article investigates the contribution of higher education to democratisation in Africa by studying the political attitudes of undergraduate students at four African flagship universities in Botswana, Kenya, South Africa and Tanzania. It analyses students’ attitudes against those of youths without higher education and mass publics in their respective countries. The study focuses on flagship universities because of their role as important players in the development of the social, economic and political leadership of their respective countries. The surveys used stratified random samples of third-year students across all faculties and years of enrolment, which resulted in a weighted sample of 400 students from each of the participating institutions. Students’ attitudes are compared with those of the same age percentiles of youths without higher education, and those of the entire population sample, from the nationwide public opinion surveys conducted by Afrobarometer. The analysis of the data uses the notions of commitment to democracy, critical citizenship and political engagement to show that students at the four flagship institutions have significantly higher levels of political awareness and political participation, and higher levels of criticalness, than youths without higher education and the general mass public. However, no consistently higher levels of commitment to democracy were found among students. We therefore argue that the study provides evidence of the political hothouse conditions typical in many African universities. It also provides grounds for the call that African higher education institutions should be more conscious of, and explicit in, the cultivation of the norms, values and practices conducive to democracy in order for higher education to contribute in enduring ways to citizenship development and the deepening of democratisation in Africa.